HUMOR LOSS IN THE SHORT FILM ONCE UPON A SNOWMAN - Moh Kavin Lidinillah (English Language Teaching Journal, 2023)
This article discusses how the humorous elements of the short animated film Once Upon a Snowman are conveyed to Indonesian by means of translation using subtitle media. The analysis in this study aims to find out whether humor in English is also considered funny in Indonesian. The results of the study show that there is complexity in translating humor using language features. The animated film Once Upon a Snowman adopts an interpretive-communicative translation method and in doing so several compromises are made. Especially through simplification which often results in a loss of humor Keywords: Humor, Translation